Q-space analysis of scattering by particles: a review - Sorensen, Christopher M. (My University, 2013)
This review describes and demonstrates the Q-space analysis of light scattering by particles. This analysis involves plotting the scattered intensity versus the scattering wave vector q = (4π/λ) sin(θ/2) on a double log plot. The analysis uncovers power law descriptions of the scattering with length scale dependent crossovers between the power laws. It also systematically describes the magnitude of the scattering and the interference ripple structure that often underlies the power laws. It applies to scattering from dielectric spheres of arbitrary size and refractive index (Mie scattering), fractal aggregates and irregularly shaped particles such as dusts. The benefits of Q-space analysis are that it provides a simple and comprehensive description of scattering in terms of power laws with quantifiable exponents; it can be used to differentiate scattering by particles of different shapes, and it yields a physical understanding of scattering based on diffraction.
Keywords: Light scattering; Scattering wave vector; Q-space analysis; Phase function; Scattering by particles; Mie theory